Hadith #4615 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hilal bin Bashr bin Mhbwb هلال بن بشر بن محبوب (Sunan Abi Dawud)
“And for this did He create them.” He said: He created these for this and those for that.
Grade: Sahih

Hadith #4624 - Sunan Abi Dawud - Hilal bin Bashr bin Mhbwb هلال بن بشر بن محبوب; Uthman bin Muslim/Sulaiman عثمان بن مسلم/سليمان بن جرموز البتي (Sunan Abi Dawud)
If we learnt that the remark of al-Hasan would reach the extent that it has reached, we would write a book for his withdrawal and call witnesses to him; but we said: This is a remark that surprisingly came out (from him) and it will not be transmitted to others.
Grade: Sahih